2020
DOI: 10.1111/gcb.15466
|View full text |Cite
|
Sign up to set email alerts
|

Declining reproductive success in the Gulf of St. Lawrence’s humpback whales (Megaptera novaeangliae) reflects ecosystem shifts on their feeding grounds

Abstract: Climate change has resulted in physical and biological changes in the world's oceans. How the effects of these changes are buffered by top predator populations, and therefore how much plasticity lies at the highest trophic levels, are largely unknown. Here endocrine profiling, longitudinal observations of known individuals over 15 years between 2004 and 2018, and environmental data are combined to examine how the reproductive success of a top marine predator is being affected by ecosystem change. The Gulf of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 76 publications
3
49
0
Order By: Relevance
“…While the external body shape of an animal is an indicator of body condition, there have been no studies that demonstrate how external body shape relates to TBD. The external body shape and lipid content of the outer blubber layer (sampled by biopsy) has a low correlation in cetaceans [44,47,48]. Our analysis confirmed that body shape is linked to buoyancy changes, explained by the proportion of total body lipid stores.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…While the external body shape of an animal is an indicator of body condition, there have been no studies that demonstrate how external body shape relates to TBD. The external body shape and lipid content of the outer blubber layer (sampled by biopsy) has a low correlation in cetaceans [44,47,48]. Our analysis confirmed that body shape is linked to buoyancy changes, explained by the proportion of total body lipid stores.…”
Section: Discussionsupporting
confidence: 69%
“…A conductivity temperature depth (CTD) profiler (miniCTD; Valeport Ltd., UK) was used to measure seawater density near tagged animals, weather permitting, within 24 h of tag deployment and within 1 km of the deployment location. Life-history traits (age class, sex, reproductive status) were assessed from field observations, photo-identification, and genetic and hormone analyses [44] of biopsy samples collected from tagged whales.…”
Section: Materials and Methods (A) Study Area And Data Collectionmentioning
confidence: 99%
“…Year 2010 marked the beginning of extremes in warmth and light ice conditions in the EGSL and other ecosystems of the North Atlantic 20 . These changes in ecosystem conditions coincided with changes in reproduction, body condition, survival rates, or distribution not only of fin whales, but of a number of other marine mammal species including St. Lawrence Estuary beluga, humpback whales, and North Atlantic right whales 47 , 57 59 .…”
Section: Discussionmentioning
confidence: 91%
“…Further research into habitat use is particularly important in light of climate change impacts (Derville et al 2018), which include variations in spatial distribution, timing of migration, behaviour (Simmonds and Eliott 2009;Cartwright et al 2019;Sousa et al 2019), reduced calving rates (Kershaw et al 2021) and likely increased mortality. The use of behavioural data provides a unique opportunity to compare habitat use between different regions along a migratory pathway, as well as between separate populations.…”
Section: Discussionmentioning
confidence: 99%